Estetika dalam Interior Cafe: Antara Fungsi dan Gaya - Imam syahri ramdhani; Safitri Fauziah Rahayu; Brynita Dayu Adesti (Imajinasi : Jurnal Ilmu Pengetahuan, Seni, dan Teknologi, 2025)
Today's cafe interiors are not only required to be comfortable, but must also have a strong visual appeal. Aesthetics and function are two important aspects that complement each other in creating a space that supports social interaction and reflects the character of the cafe itself. This study examines how design elements such as color, lighting, materials, and spatial arrangement can shape the visitor experience without ignoring the main function of the room. Using a descriptive qualitative method, this study explores examples of cafe interior designs in Indonesia that have successfully combined aesthetic values and functional needs. From the results of the analysis, it can be seen that the success of a cafe in attracting customers is greatly influenced by the balance between an attractive visual appearance and the comfort of using the space. These findings are expected to be a reference for designers and cafe owners in creating a functional space that also has strong visual characteristics.